2017
DOI: 10.1002/asia.201700450
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of Non‐ionic Twinned Amphiphiles and Their Application as Biomedical Nanocarriers

Abstract: A new class of twinned amphiphiles was developed by conjugating a pair of hydrophilic head groups from mPEG chains (M : 350 or 1000) and a pair of hydrophobic segments from linear alkyl chains (C or C ) through a novel spacer synthesized from glycerol and p-hydroxybenzoic acid. The aggregation phenomena of the amphiphiles were proven by DLS and fluorescence experiments, whereas size and morphology of the aggregates were evaluated by cryo-TEM. The measurements proved the formation of globular, thread-like or ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
(107 reference statements)
0
25
0
Order By: Relevance
“…14). 58 Depending on the amphiphile's molecular structure, globular, thread-like micelles and planar double-layer assemblies in accordance with Israelachvili's packing parameter model were observed by cryo-TEM measurements. Amphiphile 5a having relatively large hydrophobic part and short hydrophilic PEG chain resulted into planar bilayer ribbon-like aggregates.…”
Section: Twin or Dimeric Amphiphilesmentioning
confidence: 58%
“…14). 58 Depending on the amphiphile's molecular structure, globular, thread-like micelles and planar double-layer assemblies in accordance with Israelachvili's packing parameter model were observed by cryo-TEM measurements. Amphiphile 5a having relatively large hydrophobic part and short hydrophilic PEG chain resulted into planar bilayer ribbon-like aggregates.…”
Section: Twin or Dimeric Amphiphilesmentioning
confidence: 58%
“…In cell viability test, all of the amphiphiles were found to be safe for 24 h at each tested concentration. Similar types of amphiphiles were earlier measured for cytotoxic studies by our group, [49] but no significant difference was observed on cell viability on going from 24 to 72 h, thus we confined the study for 24 h at different concentrations.…”
Section: Resultsmentioning
confidence: 73%
“…As a part of our ongoing research program to synthesize a wide variety of amphiphilic nanocarrier systems capable of forming different morphological aggregates because of varied hydrophilic and hydrophobic segments, herein, we have used triglycerol, an oligomer of glycerol, as a backbone.…”
Section: Introductionmentioning
confidence: 99%